Signal transduction, receptors, mediators and genes: younger than ever : the 13th meeting of the Signal Transduction Society focused on aging and immunology - Entschladen, Frank; Altschmied, Joachim; Baumgrass, Ria; Behrmann, Iris; Giehl, Klaudia; Hermanns, Heike; Huber, Otmar; Kieser, Arnd; Klotz, Lars-Oliver; Hieke-Kubatzky, Katharina; Hass, Ralf; Janssen, Ottmar; et al. (Cell communication and signaling, 2010)
The 13th meeting of the Signal Transduction Society was held in Weimar, from October 28 to 30, 2009. Special focus of the 2009 conference was "Aging and Senescence", which was co-organized by the SFB 728 "Environmentally-Induced Aging Processes" of the University of Düsseldorf and the study group 'Signal Transduction' of the German Society for Cell Biology (DGZ). In addition, several other areas of signal transduction research were covered and supported by different consortia associated with the Signal Transduction Society including the long-term associated study groups of the German Society for Immunology and the Society for Biochemistry and Molecular Biology, and for instance the SFB/Transregio 52 "Transcriptional Programming of Individual T Cell Subsets" located in Würzburg, Mainz and Berlin. The different research areas that were introduced by outstanding keynote speakers attracted more than 250 scientists, showing the timeliness and relevance of the interdisciplinary concept and exchange of knowledge during the three days of the scientific program. This report gives an overview of the presentations of the conference.